Expansão da radiodifusão: uma análise das 1.833 outorgas do governo Temer - Pieranti, Octavio Penna [UNESP] (2021)
This paper aims to analyze the expansion of the broadcasting sector during Michel Temer’s government, based on the 1,833 new grants issued from May 2016 to December 2018. The author obtained information on the new stations by reading all editions of the Federal Official Gazette of Brazil (D.O.U.) in this period, primary source of this documentary research. We conclude that there was a wide prevalence of (a) discretionary grants and (b) mainly for private companies. There is an under-representation of new stations that could be considered as part of the public and state broadcasting systems.